Effect of omnivorous and vegan diets with different protein and carbohydrate content on growth and metabolism of growing rats. (4th July 2018) - Giuberti, Gianluca; Morlacchini, Mauro; Crippa, Luca; Capraro, Jessica; Paganini, Beatrice; Gallo, Antonio; Rossi, Filippo
Abstract: The purpose of this study was to observe, in a rat animal model, the short and medium term effects of vegan (VEG) or omnivorous (OMNI) diets with different energy partition between nutrients (zone or classic). Six different diets were administered, for 72 days to 120 growing male Sprague-Dawley rats: (i) VEG zone diet; (ii) VEG classic diet; (iii) OMNI zone diet; (iv) OMNI classic diet; (v) OMNI zone diet with added fibre and (vi) OMNI classic diet with added fibre. Zone diets (high protein and low carbohydrates), resulted in better growth, feed efficiency, lower blood glucose and insulin responses. VEG diets have lowered cholesterol blood level. Histopathological analysis evidenced no damage to liver and kidney tissue by the intake of any of the diet types. Further longer animal and human duration studies should be performed to exclude detrimental effect of higher protein diet.